A Rare Case of Turner’s Syndrome with Deaf-mutism Reporting at Government Medical College, Patiala, Punjab, India - Harshindar Kaur; anjana Saholi; Pehal Goyal; Kulwant Rai (GMC Patiala Journal of Research and Medical Education, 2021)
Abstract :Turner syndrome (TS), also known as Congenital ovarian hypoplasia syndrome, is a neurogenetic disorder characterized by partial or complete monosomy-X. Despite an often conspicuous phenotype, the diagnostic delay can be substantial and the average age at diagnosis is around 15 years of age. Morbidity and mortality are increased in women with Turner syndrome compared with the general population and the involvement of multiple organs through all stages of life necessitates a multidisciplinary approach to care. Treatment may include growth hormone therapy at appropriate time for short stature and estrogen therapy to help stimulate sexual development.